Application of Andragogical Principles in the Catfish Cultivation Training Program at the Nanggalo District Office, Padang City - Tanwir Klub Harahap, Mhd; Jamaris, Jamaris; Setiawati, Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
The problem of this study is the high motivation of the trainee in following a training activity of catfish farming in the District Office Nanggalo Padang. The purpose of this study is to provide an overview of gestures sources, provide a snapshot view of contact sources and give gamabaran dress informant. This type of research is descriptive quantitative research. The population in this study were all trainees catfish totaling 30 people, and samples were taken as much as 65% of 20 people, with sampling techniques stratified random sampling. The data collection technique used was a questionnaire, while the means of collecting data using questionnaires. Data were analyzed using a percentage formula. The results showed that: (1) the application of the principles of andragogy in speaker performance on aspects of body movement is very good; (2) the application of the principles of andragogy in speaker performance on aspects of eye contact is very good; (3) the application of the principles of andragogy in performance speakers on catfish farming training program on the aspects of hand gestures is very good.Keywords : Principles of Andragogy, Mitivation